Green human resource management for urban sustainability: Transforming work culture towards smart green cities - Sultan, Zulkifli; Safitri, Julia; Pariyanti, Eka; Mukhtar, Afiah; Nurlaila, Nurlaila (Asian Management and Business Review, 2026)
This study aims to develop a strategic model of green human resource management (GHRM) to support the realization of smart green cities by fostering a green work culture and promoting environmentally friendly sustainable practices. Using a quantitative approach, data were collected through questionnaires from 400 respondents in four major Indonesian cities: Makassar, South Tangerang, Bandung, and Denpasar. Structural equation modeling (SEM) was used to analyze the relationship between GHRM, work culture, environmental quality, and smart green city development. The research results show that GHRM plays a role in shaping an environmentally oriented work culture and improving environmental quality. These two factors have proven to be the main pathway connecting GHRM policies to the realization of smart green cities. These findings confirm that the success of a smart green city is determined not only by GHRM policies, but also by concrete actions and cross-sector collaboration between organizations, government, and the community.